Dual fuel combustion in a CI engine powered by blended diesel-biodiesel fuel and simulated gasification gas - Mahgoub, B.K.M. (Asian Research Publishing Network, 2016)
The objective of this study was to investigate the performance of dual fuel combustion in a compression ignition engine powered by blend diesel/palm oil biodiesel (50:50) and simulated gasification gas. The in-cylinder pressure data was collected for each crank angle in order to investigate the combustion characteristics at constant half load over a range of pilot fuel substitution rate. Substantial differences in the in-cylinder peak pressure occurred and three phases of the dual fuel combustion process were clearly seen in the heat release rate curves when the engine load was maintained at half load. Maximum cylinder pressure was obtained with syngas dual fuelling at lower substitution rates. Lower engine efficiency of 33.84 was observed with syngas dual fuelling at the highest substitution rate of pilot fuel (28). Â© 2006-2016 Asian Research Publishing Network (ARPN).